European Security in the Context of Migration - Measures to Protect Borders and Security Aspects Connected with Migration - Kesel, Juraj (European Scientific Journal, ESJ, 2017)
The aim of this article is to assess the existing development of migrant crisis in connection with the divided member states of the European Union. Based on the comparison of migrant flows, study of the measures adopted in order to prevent migration and analysis of security risks of migration presented in the article it has been proven that there is a direct correlation between migration and an increased rate of terrorist attacks in Europe. The elimination of smuggling groups and the support of migrants' countries of origin have helped to mitigate migration pressure. The outcomes of the article confirm that despite the adoption of legal and technical measures by the European Union in order to secure the external border of the Schengen Area, European countries do not share the same view of how to solve the migrant crisis. The outcome of migration issue solution is to provide relevant information to the expert public in order to support a stable and safe European Union. It is an equal partnership of all the European Union member states in all the areas that is of the highest priority in order to guarantee the above state.